A HUMANISTIC APPROACH TO EDUCATION: A SYSTEMATIC REVIEW OF THE BOOK THE BEST SCHOOLS BY THOMAS ARMSTRONG - Zam Zami, Muhammad Assyauqi; Kibtiyah, Asriana (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Thomas Armstrong’s book, The Best Schools, offers a profound critique of the conventional education system, which places excessive emphasis on academic achievement and standardized test results while neglecting the holistic development of students. Armstrong proposes a humanistic educational paradigm that prioritizes the comprehensive growth of learners, encompassing physical, cognitive, social, emotional, and spiritual dimensions. The book elaborates on how principles of human development can be translated into practical and relevant educational practices across different levels of schooling, from early childhood to senior high school. This study systematically reviews Armstrong’s educational concepts and practices, examining their relevance and potential application in the context of Indonesian education. The findings indicate that a humanistic approach, which values the uniqueness and developmental needs of each individual, effectively enhances learning motivation, socio-emotional skills, and students’ psychological well-being. Furthermore, this approach fosters an inclusive, supportive, and democratic learning environment, which is essential for nurturing students who are not only academically competent but also emotionally mature and prepared to face global challenges. The study recommends the integration of Armstrong’s principles into Indonesian educational policies and practices as part of a more humane and meaningful educational reform.